(3EOGQI JZjjQ GdCaQGO hGdCOGA(B; (3cja?(B"(3GdeHGOF(B-(3GdESJQGJjLjGJ(B-(3GdQDi (B:s (3YTQI eHGOF dJaYjd EOGQI GdJZjQ (B/s - (3c(B.(3SejK, OhLdGSs; (3GdNRGej, YHO GdMce CMeO s ((3GdbGgQI(B: s (3GjJQGc ddfTQ hGdJhRjY(B, s, 2001)
(3GdeHGOF (B-(3GLJjGR aJQI GdJYHjQ HfLGM(B-(3JLfjO GdCaQGO ef CLd GdCOGA hGdJZjjQ(B-(3fJGFL GdCOGA(B:(3EOGQI GdQHW Hjf GdaQU hGdJZjjQ(B-(3GdCaQGO GdMGdjhf hGdSdhcjGJ GdLOjOI gd JhGLg gPG GdJMOj(B-(3GdPgGH Edi eG hQGA GdbQGQGJ hGdhYj Edi GdCOGA hGdJZjjQ(B-(3GdeHGOdI hGdJHGOd hGdJfSjb(B-(3UjGZI hGQJLGd GdGSJQGJjLjI GdfGLMI (B-(3GGdQDi (B-(3GdWGbI hGddZI PGJ GdeZRi(B-(3EYGOI QHW JUejeGJ GdefXeI HeG jJdGFe eY GdCaQGO hGdCOGA hGdYed(B-(3EYOGO QDjJc GdTNUjI dYedjI GdJZjjQs
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQI GdYGeIs